REACTUALIZATION THE AUDIOLINGUAL APPROACH THROUGH ‘IRENG MANIS’S INNOVATIVE MODEL FOR IMPROVING THE STUDENT ABILITY OF UNGGAH-UNGGUH BASA IN SENIOR HIGH SCHOOL - Rakhmawati, Ani; Istiana, Rahayu Nur (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The teaching and learning Javanese language in high school during the covid-19 pandemic is challenging due to the limitations of face-to-face between teachers and students. The application of an innovative learning model called 'ireng manis' aims to overcome various obstacles in achieving Javanese language proficiency. The learning model of Ireng Manis (an acronym for mireng, nggunem, maca, lan nulis) is essentially a re-actualization of the audiolingual approach that is expected to incorporate all four areas of language skills, including listening, speaking, reading, and writing. Ireng Manis's innovative model uses memorization, practice, and repeat strategies. This model is designed by combining students' grammar and communicative competence in applying 'manners', a type of Javanese commonly used to respect older or more knowledgeable people. The technique is carried out by utilizing the development of communication technology, namely the application of chat menus (chat) and voice (voice) on WhatsApp as a learning medium. Keywords: the audiolingual approach, ‘ireng manis’ innovative model